Upodobitve simetričnih grup - Miščič, Matevž (Matrika, 2022)
In this paper representation theory of finite groups is presented. Irreducible representations are defined and it is shown that every representation of a finite group is a direct sum of irreducible representations. All irreducible representations of symmetric groups are classified.
Keywords: finite groups; končne grupe; representation theory; simetrične grupe; symmetric groups; upodobitve grup